Exploring the Foundations of Peace: An Analytical Study of the Concept of Peace in Islam with Emphasis on the Qurʼān and the Sīrah of Prophet Muhammad (SAW) - Khan, Gawhar Ahmad (al-Afkar, Journal For Islamic Studies, 2025)
Examining the Qurʼān and Prophet Muhammad’s (SAW) Sīrah, this study explores the core of peace in Islam. It explains how Islamic teachings on peace are complex through a careful examination of important scriptures and historical settings. In Islam, peace extends beyond the mere absence of violence and includes justice, balance, and spiritual tranquility. The idea of peace is emphasized throughout the Qurʼān as a vital guide for people, societies, and countries to coexist together. The life of the Prophet Muhammad (SAW) is an example of compassion, tolerance, and moral behavior in a variety of settings, making it a beacon of peace. In order to promote and maintain peace, harmony, and brotherhood, the study will examine Islamic concepts in this respect. In order to emphasize the importance of peace in Islam, it will analyze the main sources of Islamic knowledge, including the Qur'an, the Sunnah, and the Sīrah of the Prophet Muhammad (SAW).